Geriatric Emergency Department Innovations: Preliminary Data for the Geriatric Nurse Liaison Model. Issue 9 (12th August 2014) - Aldeen, Amer Z.; Courtney, D. Mark; Lindquist, Lee A.; Dresden, Scott M.; Gravenor, Stephanie J.; the GEDI‐WISE Investigators
<x xml:space="preserve">Abstract</x> Older adults account for a large and growing segment of the emergency department (ED) population. They are often admitted to the hospital for nonurgent conditions such as dementia, impaired functional status, and gait instability. The aims of this geriatric ED innovations (GEDI) project were to develop GEDI nurse liaisons by training ED nurses in geriatric assessment and care coordination skills, describe characteristics of patients that these GEDI nurse liaisons see, and measure the admission rate of these patients. Four ED nurses participated in the GEDI training program, which consisted of 82 hours of clinical rotations in geriatrics and palliative medicine, 82 hours of didactics, and a pilot phase for refinement of the GEDI consultation process. Individuals were eligible for GEDI consultation if they had an Identification of Seniors At Risk (ISAR) score greater than 2 or at ED clinician request. GEDI consultation was available Monday through Friday from 9:00 a.m. to 8:00 p.m. An extensive database was set up to collect clinical outcomes data for all older adults in the ED before and after GEDI implementation. The liaisons underwent training from January through March 2013. From April through August 2013, 408 GEDI consultations were performed in 7, 213 total older adults in the ED (5.7%, 95% confidence interval (CI) = 5.2–6.2%), 2, 124 of whom were eligible for GEDI consultation (19.2%, 95% CI = 17.6–20.9%); 34.6% (95% CI = 30.1–39.3%) received social work consultation, 43.9% (95% CI = 39.1–48.7) received pharmacy consultation, and more than 90% received telephone follow‐up. The admission rate for GEDI patients was 44.9% (95% CI = 40.1–49.7), compared with 60.0% (95% CI = 58.8–61.2) non‐GEDI. ED nurses undergoing a 3‐month training program can develop geriatric‐specific assessment skills. Implementation of these skills in the ED may be associated with fewer admissions of older adults.